Evolution of the tetrapyrrole synthesis in eukaryotes - Kořený, Luděk (Jihočeská univerzita, 2011)
This thesis focuses on the nature of heme metabolism in various eukaryotes. One of the aims was the elucidation of the origin of the unique heme biosynthesis pathway in apicomplexan parasites through a comparative study of their photosynthetic relative Chromera velia combining molecular biology, biochemistry and bioinformatics approach. Using similar strategy, I have also investigated the origin and spatial organization of tetrapyrrole biosynthesis in Euglena gracilis. Based on the phylogenetic data I described the complex evolution of heme metabolism in kinetoplastid flagellates including pathogenic trypanosomes. I revealed that one of them (Phytomonas) does not require heme for viability by the combination of various biochemical and molecular biology experiments and bioinformatic analyses.
Evolution of the tetrapyrrole synthesis in eukaryotes
Keywords: Heme synthesis; Tetrapyrrole pathway; Evolution; Eukaryotes; Endosymbioses; Parasites; Heme synthesis; Tetrapyrrole pathway; Evolution; Eukaryotes; Endosymbioses; Parasites